THE IMPORTANCE OF TEACHER’S WRITTEN FEEDBACK ON THE STUDENTS’ WRITING IN TEACHING LEARNING PROCESS - Afifah Raihany (OKARA: Jurnal Bahasa dan Sastra, 2014)
Teacher’s feedback to the student’s writing is vital for improving both teaching and learning process. It enables the teachers to find out to what extent they have been successful in their teaching and what they need to do to make their teaching more effective. Feedback also influences learning in that it provides an opportunity for learners mainly EFL learners to know what they need to do in order to improve. Unfortunately, the teachers’ responses to the student’ writing is sometimes neglected. In other words, they may pay little attention to the students’ views or opinions about forms/ types of teachers’ feedback they receive. Thus, the teachers do not know the students’ problems in responding to the teachers’ feedback and they do not know the students’ views of what forms and types of response the students prefer or even the teachers do not know much how to react in order to help the students process feedback successfully.